Risk assessment of Campylobacter spp. in broiler chickens : technical report (WHO, 2009)
Campylobacter is a leading cause of enteric infections in many countries. The principal reservoir of pathogenic Campylobacter spp. is the alimentary tract of wild and domesticated mammals and birds. Poultry meat is an important vehicle for foodborne transmission of Campylobacter spp., particularly Campylobacter jejuni. FAO and WHO have undertaken a risk assessment of Campylobacter spp. in broiler chickens. This assessment compared the risk for a variety of scenarios and mitigation measures for control of the organism in a range of broiler chicken products. It also includes a review and analysis of current scientific information and a description of the risk model. This volume and others in this Microbiological Risk Assessment Series contain information that is useful to both risk assessors and risk managers, the Codex Alimentarius Commission, governments and food regulatory agencies, industry and other people or institutions with an interest in Campylobacter spp. in broiler chickens, the public health impact and the use of risk assessment in the evaluation and selection of potential control strategies.
Microbiological risk assessment series, ISSN 1726-5274 No. 12
Keywords: zemědělství a potravinářství; hygiena; hodnocení rizik; kontaminace potravin; mikrobiologie, lékařská mikrobiologie; bakteriologie; Risk Assessment; Campylobacter; Bacteriology; Food Contamination